Electron‐Stimulated Aluminum Nitride Crystalline Phase Formation on the Sapphire Surface. Issue 6 (15th February 2019) - Milakhin, Denis; Malin, Timur; Mansurov, Vladimir; Galitsyn, Yury; Zhuravlev, Konstantin
Abstract : The effect of a high‐energy electron beam (11 keV) on the (0001) sapphire nitridation process is investigated. The high‐energy electrons accelerate more than an order of magnitude the sapphire nitridation process. The effect is due to an increase of the Al and N atom concentrations on the sapphire surface caused by the electron‐stimulated desorption of oxygen atoms and electron‐stimulated decomposition of ammonia molecules. Abstract : In this article, the effect of a high‐energy electron beam on the sapphire nitridation process is investigated. The mechanisms of the influence are discussed. Investigations show that, when the electron beam influence is excluded, the AlN formation process is slower and differs by more than an order of magnitude from the nitridation process under an intense continuous beam action.